El sistema de CAUSACIÓN en las cláusulas mentales y relacionales del bribri según la gramática sistémico-funcional - Cruz Volio, Gabriela (2014)
This article analyses the AGENCY system that takes place in mental and relational clauses of Bribri (Coroma’s variation) according to Halliday’s systemic-functional grammar (2004). The main objective is to describe the codification of mental and relational processes and their associated participants through the analysis of five Bribri texts. Since processes and participants are part of the TRANSITIVITY system (which includes the TYPE OF PROCESS and AGENCY subsystems), the present study also describes this system.